2020
DOI: 10.1111/jfpe.13486
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of drying and rehydration kinetics ofRosa pimpinellifoliafruits: Toward formulation and optimization of a new tea with high antioxidant properties

Abstract: Rosa pimpinellifolia is the black of rosehips having many uses in the food and pharmaceutical industries. The modeling of drying and rehydration kinetics of the fruits as well as the optimization of preparation conditions of a new tea was investigated. Empirical models were applied to predict the drying and rehydration behaviors of R. pimpinellifolia fruits. Response surface methodology was used to optimize the tea preparation together with antioxidant properties. The analysis of drying behavior of the fruits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 70 publications
8
30
0
Order By: Relevance
“…Our results are consistent with previous studies which have reported these models to be adequate to predict the rehydration behavior of food products (Benseddik et al, 2019; Dadali, Demirhan, & Özbek, 2008; Goula & Adamopoulos, 2009; Noshad, Mohebbi, Shahidi, & Mortazavi, 2012). In addition, Pashazadeh et al (2020) have reported that Peleg, Vegá‐galves and Weibull models depicted better the rehydration behavior of black rosehip at 20, 40, and 60°C.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Our results are consistent with previous studies which have reported these models to be adequate to predict the rehydration behavior of food products (Benseddik et al, 2019; Dadali, Demirhan, & Özbek, 2008; Goula & Adamopoulos, 2009; Noshad, Mohebbi, Shahidi, & Mortazavi, 2012). In addition, Pashazadeh et al (2020) have reported that Peleg, Vegá‐galves and Weibull models depicted better the rehydration behavior of black rosehip at 20, 40, and 60°C.…”
Section: Resultsmentioning
confidence: 96%
“…The width and length of the fresh fruits were determined with a micrometer and the water activity was measured with a water activity meter (Aqualab 4TE). The total soluble solids were determined by homogenizing 10 g of crushed fruit with 20 ml of distilled and the mixture was read with a digital refractometer at room temperature (20°C; Pashazadeh, Zannou, & Koca, 2020). The pH was directly measured in mixture prepared for total soluble solids using a glass electrode pH meter.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations